Pengaruh Pelaksanaan Self Assessment System Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Pada Penerimaan Pajak Restoran Di Badan Pendapatan Daerah Kabupaten Gorontalo - Lantowa, Felmi D; Radjak, Lukfiah I; Ilham, Magfira (JSAP : Journal Syariah and Accounting Public, 2024)
This research aims to determine "The Effect of Implementing the Self Assessment System and Tax Sanctions on Taxpayer Compliance in Restaurant Tax Revenue at the Regional Revenue Agency of Gorontalo Regency". This research is quantitative research using primary data obtained by distributing questionnaires to 87 taxpayers who were used as research samples. The data analysis technique uses multiple linear regression analysis. The research results show that partially the Self Assessment System has a significant effect on taxpayer compliance, as well as tax sanctions have a significant effect on taxpayer compliance. Simultaneously, the Self Assessment System and Tax Sanctions together have a significant effect on taxpayer compliance with restaurant tax revenues in the Gorontalo district regional revenue agency